2023
DOI: 10.1098/rstb.2022.0164
|View full text |Cite
|
Sign up to set email alerts
|

SCN5A channelopathy: arrhythmia, cardiomyopathy, epilepsy and beyond

Abstract: Influx of sodium ions through voltage-gated sodium channels in cardiomyocytes is essential for proper electrical conduction within the heart. Both acquired conditions associated with sodium channel dysfunction (myocardial ischaemia, heart failure) as well as inherited disorders secondary to mutations in the gene SCN5A encoding for the cardiac sodium channel Nav1.5 are associated with life-threatening arrhythmias. Research in the last decade has uncovered the complex nature of Nav1.5 dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 179 publications
(266 reference statements)
1
9
0
Order By: Relevance
“…Some studies have shown that SPOCD1 [577], DRD3 [578], DOCK5 [579], SLCO6A1 [305], HTR2C [580], OTX2 [581], LMX1A [582], NR2E1 [319], GPR78 [323], RORB (RAR related orphan receptor B) [583], NTNG2 [326], PRR5-ARHGAP8 [584], CACNA2D4 [585], SLC1A2 [586], CUX2 [587], KCNH7 [588] and ACAN (aggrecan) [335] plays a certain role in bipolar disorder. The altered expression of ABCG2 [589], LAMC3 [590], CACNA1A [591], COL6A2 [592], SLC13A5 [593], GABRA2 [594], SCN5A [160], KCNQ5 [595], SLC1A2 [596], TRPC3 [597], GABRA4 [598], SLC6A11 [599], KCNQ5 [600] and SLCO5A1 [601] are associated with epilepsy. In summary, DEGs involved in GO term and REACTOME pathway were more likely related to schizophrenia and might be important targets in schizophrenia therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that SPOCD1 [577], DRD3 [578], DOCK5 [579], SLCO6A1 [305], HTR2C [580], OTX2 [581], LMX1A [582], NR2E1 [319], GPR78 [323], RORB (RAR related orphan receptor B) [583], NTNG2 [326], PRR5-ARHGAP8 [584], CACNA2D4 [585], SLC1A2 [586], CUX2 [587], KCNH7 [588] and ACAN (aggrecan) [335] plays a certain role in bipolar disorder. The altered expression of ABCG2 [589], LAMC3 [590], CACNA1A [591], COL6A2 [592], SLC13A5 [593], GABRA2 [594], SCN5A [160], KCNQ5 [595], SLC1A2 [596], TRPC3 [597], GABRA4 [598], SLC6A11 [599], KCNQ5 [600] and SLCO5A1 [601] are associated with epilepsy. In summary, DEGs involved in GO term and REACTOME pathway were more likely related to schizophrenia and might be important targets in schizophrenia therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This drives the rapid depolarizing activating phase 0 of the consequent atrial or ventricular cardiomyocyte APs. Nav1.5 shows complex functional and distribution patterns among subcellular cardiomyocyte subdomains; cardiomyocytes may further express additional Nav1.x subtypes ( Remme, 2023 ). Subsequent I Na inactivation contributes to AP recovery alterable by pathological persistent, potentially pro-arrhythmic, late, I NaL , currents ( Chadda et al, 2017 ; Yu et al, 2018 ; Liu et al, 2023 ).…”
Section: Ion Channels Underlying Normal and Abnormal Rhythmic Activitymentioning
confidence: 99%
“…At intercalated disks, Nav1.5 associates with N-cadherin, connexin-43, β IV -spectrin, and desmosomal proteins including plakophilin-2 and desmoglein-2. Gene mutations involving some of these proteins are associated with arrhythmic disorders suggesting Nav1.5 dysfunction ( Shy et al, 2013 ; Remme, 2023 ).…”
Section: Ion Channel Modulation At the Level Of The Cell Membranementioning
confidence: 99%
“…In the current theme issue, Salvage et al . [ 24 ], Remme [ 25 ], Terrar [ 26 ], Jung et al . [ 27 ] and He et al .…”
Section: Modern Developments In the Fieldmentioning
confidence: 99%
“…Furthermore, electrophysiological aberrations and arrhythmic tendency in the BrS and LQTS3 models were similarly accentuated or relieved by flecainide and ameliorated or accentuated by quinidine [ 53 , 60 ], findings with potential translational significance [ 61 , 62 ]. Remme [ 25 ] reviews complex Nav1.5 functional and distribution patterns involving particular subcellular cardiomyocyte subdomains, as well as non-canonical non-electrogenic Nav1.5 actions with structural, potentially cardiomyopathic and pro-arrhythmic, effects. Finally, Nav1.5 does occur in other cell types, including various extracardiac tissues.…”
Section: Ion Channels Contributing To Cardiomyocyte Surface Membrane ...mentioning
confidence: 99%